2020
DOI: 10.31234/osf.io/5a34k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Facet-Level Personality Development in the Transition to Adolescence: Maturity, Disruption, and Gender Differences

Abstract: The transition to adolescence is marked by enormous change in social, biological, and personality development. Although accumulating evidence has offered insight into the nature of higher-order personality trait development during this period, much less is known about the development of lower-order personality traits, or “facets”. The current study employed a cohort- sequential longitudinal design to examine domain- and facet-level trajectories for mother- reported personality traits during the early adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 78 publications
3
10
0
Order By: Relevance
“…• Adaptive development generally occurs from late adolescence (e.g., Klimstra et al, 2018;Luan et al, 2018) up to the years preceding death (e.g., Wagner et al, 2016), with changes that are most pronounced in emerging adulthood (ages 18-30; Roberts & Davis, 2016). However, in some samples, adaptive development begins earlier in life (e.g., Brandes et al, 2020) and extends into very old age (e.g., Mueller et al, 2016). • On average, traits only co-mature within people to a small extent, as adaptive development in one trait is mostly independent of adaptive development in others (e.g., Allemand & Martin, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…• Adaptive development generally occurs from late adolescence (e.g., Klimstra et al, 2018;Luan et al, 2018) up to the years preceding death (e.g., Wagner et al, 2016), with changes that are most pronounced in emerging adulthood (ages 18-30; Roberts & Davis, 2016). However, in some samples, adaptive development begins earlier in life (e.g., Brandes et al, 2020) and extends into very old age (e.g., Mueller et al, 2016). • On average, traits only co-mature within people to a small extent, as adaptive development in one trait is mostly independent of adaptive development in others (e.g., Allemand & Martin, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for the observed weighted average of d z = .22 might be that desirable personality change resulted not from participation in arts education but from normative changes in personality (for normative changes, see e.g., Brandes et al, 2020; Orth et al, 2018). To investigate this possibility, we compared the weighted average d z of the treated groups with the weighted average d z of the control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a word on normative personality developments during childhood and adolescents is in order. First, the maturity principle proposes conscientiousness, emotional stability, and agreeableness increase with age (e.g., Brandes et al, 2020; Caspi et al, 2005). Second, the disruption hypothesis states that biological, social, and psychological changes lead to a setback in desirable personality traits (i.e., conscientiousness and agreeableness) during adolescence (e.g., Brandes et al, 2020; Soto & Tackett, 2015).…”
Section: A Review Of Empirical Studies On Arts Education and Personal...mentioning
confidence: 99%
See 1 more Smart Citation
“…Rank-order stability reflects the degree to which the relative ordering of individuals on shyness is maintained over time, whereas mean-level change refers to changes in the average level of shyness in a population. Previous studies examining the rank-order stability of shyness have found moderate to high levels of stability across adolescence (test–retest correlations of .56–.67 for 4–5 years) when shyness was assessed using parent-reports (Brandes et al, 2020; Karevold et al, 2012; Laceulle et al, 2012). Youth self-reported shyness tends to show lower, but still moderate, rank-order stability, such as 1-year test–retest correlations of .58 to .62 and a 2-year correlation of .52 from age 10 to 12 (Hassan et al, 2021).…”
Section: Shynessmentioning
confidence: 97%